Asbab an-Nuzul : Pengertian, Macam-Macam, Ungkapan, Urgensi dan Kegumaan - Nisa, Alifia Khoirun (Maliki Interdisciplinary Journal, 2024)
Some scholars, such as Shubhi Shalih and Manna' Khalil Al-Qattan, differ in explaining asbab al-nuzul. Everyone agrees that asbab al-nuzul is an event or incident that prompts the revelation of a verse of the Quran to answer, explain, and solve problems that arise as a result of the event. Asbab an-nuzul is historical material that can be used to explain the revelation of Quranic verses and provide context for understanding its injunctions. Of course, these materials only include events that occurred during the time of the Quran's revelation (ashr at-tanzil). There are two types of asbab al-nuzul: Ta'addud Al-Asbab Wa Al-Nazil Wahid and Ta'adud an-nazil wa al-asbab wahid. Not all redactions or expressions used by the Companions indicate how the Quran was revealed. The two main redaction categories are Sarih (clear) and Muhtamilah (vague). Asbab an-nuzul is an important component in the process of interpreting the Quran. One will not be able to understand the situation in which a verse was revealed, if they do not understand the history of its asbab al-nuzul. Verses must be applied in various situations.